2009
DOI: 10.1097/brs.0b013e3181b61955
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility Measuring the Angle of Proximal Junctional Kyphosis Using the First or the Second Vertebra Above the Upper Instrumented Vertebrae in Patients Surgically Treated for Scoliosis

Abstract: Good reproducibility and agreement using the first and second vertebrae above the UIV to measure the angle of PJK was found in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Sacramento-Dominguez et al [16] evaluated the reproducibility of measuring the Cobb angle of PJK using either the first or the second vertebra above the UIV in 19 scoliosis patients. Intra-surgeon concordance correlation coefficients ranged from 0.78 to 0.92 (high to very high reproducibility) and comparative inter-surgeon concordance correlation coefficients ranged from 0.55 to 0.80 (moderate to high reproducibility).…”
Section: Definitionmentioning
confidence: 99%
“…Sacramento-Dominguez et al [16] evaluated the reproducibility of measuring the Cobb angle of PJK using either the first or the second vertebra above the UIV in 19 scoliosis patients. Intra-surgeon concordance correlation coefficients ranged from 0.78 to 0.92 (high to very high reproducibility) and comparative inter-surgeon concordance correlation coefficients ranged from 0.55 to 0.80 (moderate to high reproducibility).…”
Section: Definitionmentioning
confidence: 99%
“…Although they demonstrated moderate to very high intra-and inter-rater reliability, the authors could not conclude which of the two vertebrae is the better landmark to use for measuring PJK [36]. Further work has recently shown that radiographic measurement of kyphosis from UIV to UIV+2 is highly repeatable, with or without presence of PJF and at either upper thoracic or thoracolumbar junction [37].…”
Section: Definition Epidemiology and Clinical Significancementioning
confidence: 99%
“…Sacramento-Dominguez et al [36] evaluated the reproducibility of using the UIV+1 and UIV+2 to measure PJK. Although they demonstrated moderate to very high intra-and inter-rater reliability, the authors could not conclude which of the two vertebrae is the better landmark to use for measuring PJK [36].…”
Section: Definition Epidemiology and Clinical Significancementioning
confidence: 99%
“…He received 2-staged Smith-Petersen osteotomies with partial rib resections bilaterally, cervical traction, cantilever kyphosis correction, manual intraoperative reduction, and instrumented posterior fusion extension. (5) compression fracture at the upper instrumented vertebra, (6) instrumentation failure at the proximal construct, or (7) facet violation. 1 , 15 , 16 The development of PJK is unknown but is likely multifactorial.…”
Section: Discussionmentioning
confidence: 99%